2005
DOI: 10.1002/dvdy.20625
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish id2 developmental expression pattern contains evolutionary conserved and species‐specific characteristics

Abstract: The inhibitor of differentiation or inhibitor of DNA binding (Id) family are members of the helix-loop-helix (HLH) group of transcription factors that play important roles in cell proliferation, differentiation, cell cycle control, and apoptosis. They modulate the formation of active class A-class B basic HLH (bHLH) complexes. Ids lack the amino-terminal associated basic region necessary for DNA binding, thus sequestering the class A factors, inhibiting the formation of active class A-class B heterodimers and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…This results in inhibition of transcription of genes – targets of positive MRFs [63,64]. Overexpression of id2 [65] in a one-sided fashion resulted in the downregulation of cxcr4a or sdf1a transcription (Figures 6F, F', O, P–P"'). Taken together, these data suggest that myoD or myf5 act in parallel with their co-factors to regulate transcription of cxcr4a or sdf1a .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This results in inhibition of transcription of genes – targets of positive MRFs [63,64]. Overexpression of id2 [65] in a one-sided fashion resulted in the downregulation of cxcr4a or sdf1a transcription (Figures 6F, F', O, P–P"'). Taken together, these data suggest that myoD or myf5 act in parallel with their co-factors to regulate transcription of cxcr4a or sdf1a .…”
Section: Resultsmentioning
confidence: 99%
“…The odysseus ( ody J10049 /cxcr4b) mutants and myosin light chain 2 ( mylz2 -GFP) transgenics were described [6,41]. Pigment formation was blocked with 1-phenyl-2-thiourea (PTU) [65]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…142 Recent studies examining Notch and Delta mutant zebrafish embryos revealed relatively normal levels of Id2 expression indicating that other Notch receptors/ligands may be involved or alternatively, various Notch and Delta components might be necessary to cooperatively regulate Id2. 143 The recently reported CBF-1/RBP-J-independent Notch/ R-Ras pathway 68 may also be relevant to VSMC phenotypic switching and VSMC differentiation. In differentiated cells, insulin-like growth factor 1 is required for maintaining the differentiated phenotype 69 and through an IRS-1/SHP-2 Ras activation that acts as a switch controlling VSMC phenotypedependent signaling.…”
Section: Notch and Id Functionmentioning
confidence: 99%
“…All were down-regulated at 52 hpf except tfap2a, which was suppressed at both 36 and 52 hpf. These factors generally control genes involved in the balance between proliferation and differentiation of many cell types, including those of the neural retina (24)(25)(26). Many (tfap2a, tfap2b, tfap2c, and id2) have been shown to express in specific regions of the retina (24, 27, 28).…”
Section: Functional Validations Of Brg1-regulated Retinal Differentiamentioning
confidence: 99%